Growth, yield, and land use efficiency of soybean-maize relay cropping under saturated soil culture on tidal swamps - Sahuri, Sahuri; Munif Ghulamahdi; Suwarto (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2023)
More than 75 percent of households growing maize and soybean adopts the monoculture method. The relay cropping of soybean-maize is a strategic choice to increase the planted area and productivity of these two commodities' sustainability in tidal swamps. The research aimed to study the land equivalent ratio (LER), determine the best planting spacing and soybean varieties, and the best relay cropping of maize on saturated soil culture in tidal swamps. The experiment was on mineral soils with type B tidal swamps, in Banyuasin, South Sumatra, from July to December 2022. The experiment used a three-factor randomized complete block design with three replications. The first factor was soybean varieties: Argomulyo, Gepak Kuning, Detap 1, and Demas 1, the second factor was soybean planting spacing: 78 cm x 15 cm x 12.5 cm and 60 cm x 40 cm x 10 cm, and the third factor was the relay cropping of maize: 30 and 45 days after planting (DAP) of soybeans. Results showed that plant height, number of leaves, number of branches, filled pods, 100 seeds weight, and seed yield were influenced significantly by varieties. Demas 1 variety produced a higher seed yield, with relay cropping and monoculture, i.e., 4.2 tons ha-1 and 4.1 tons ha-1, respectively. Plant height, stem diameters, number of leaves, 100 grains weight, and grain yield in maize were significantly higher at soybean planting spacing of 78 cm x 15 cm x 12.5 cm and relay cropping at 30 DAP. The LER values > 1, indicated that relay cropping increased land productivity as compared to monoculture cultivation. The LER at relay cropping of 30 DAP was significantly highest for Argomulyo and Detap 1 varieties, i.e., 1.8 and 1.8, respectively. Keywords: Land equivalent ratio, planting spacing, relay cropping, saturated soil culture, tidal swamps